Fatty Acid Content in Biomasses: State-of-the-Art and Novel Physical Property Estimation Methods - Ana M. Sousa; Thalles A. Andrade; Massimiliano Errico; José P. Coelho; Rui M. Filipe; Henrique A. Matos (International Journal of Chemical Engineering)
In line with the growing environmental awareness developed along the last decades, modern societies are urged to evolve into sustainable economics where the reuse of organic wastes represents the key feedstock for a green transaction. The oil phase obtained from different biomasses has the potential to be a source of food supplements, medicines, cosmetics, or feedstock for biofuel production. In the present work, the composition of 104 different biomasses including seeds, peels, flowers, plants, and leaves has been reviewed for the lipid content. Based on the most frequent fatty acids screened, experimental data for normal boiling point temperature, normal melting point, critical properties, and acentric factor were collected and compared with the most common estimation methods, which are functions of the molecular structure and interaction between different functional groups. New predictive equations have been proposed to reduce the estimation deviation and to provide simple correlations to be used in simulation software when dealing with biomass processes. For all the properties, the estimations proposed have an absolute average deviation equal to or lower than 4.6%.